First-Line Carboplatin, Pemetrexed, and Panitumumab in Patients with Advanced Non-Squamous KRAS Wild Type (WT) Non-Small-Cell Lung Cancer (NSCLC). (14th September 2017) - Spigel, David R.; Mekhail, Tarek M.; Waterhouse, David; Hadley, Terence; Webb, Charles; Burris, Howard A.; Hainsworth, John D.; Greco, F. Anthony
ABSTRACT: Background: We added panitumumab to standard combination chemotherapy as first-line treatment for patients with advanced KRAS WT non-squamous NSCLC. Methods: Patients received panitumumab 9 mg/kg IV, pemetrexed 500 mg/m 2 IV, and carboplatin AUC = 6 IV every 21 days. After 6 cycles, maintenance therapy with panitumumab and pemetrexed was administered every 21 days until progressive disease or unacceptable toxicity. Results: 29 of 66 patients (44%) had objective responses. The median TTP was 6 months; median overall survival (OS) was 17 months. Panitumumab increased treatment-related toxicity, notably skin rash. Conclusions: The addition of panitumumab increased toxicity, and had no discernible impact on efficacy.